2013
DOI: 10.1017/s175173111200167x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sex and immunocastration on feed intake behavior, skatole and indole concentrations in adipose tissue of pigs

Abstract: Feed intake behavior was studied between 9 weeks of age and slaughter in a total of 36 gilts, 32 immunocastrates, 33 surgically castrated barrows and 33 boars from 36 litters. Consequences for the concentration of substances contributing to off odor of pork (skatole, indole) were evaluated. Animals were kept in groups of 12 pigs of the same sex and treatment and fed ad libitum (13.4 MJ ME, 17% CP, 1.1% lysine). Individual feed intake behavior was recorded continuously by an electronic feeder. Immunocastration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 39 publications
2
40
0
3
Order By: Relevance
“…This is a result of lower feed intake without clear differences in ADG. After the second vaccination, however, ADFI and DG of IM strongly increases (Schmidt et al, 2011;Batorek et al, 2012b;Weiler et al, 2013). We showed that this increase is very abrupt and noticeable within 1 week after the second injection.…”
Section: Discussionmentioning
confidence: 63%
“…This is a result of lower feed intake without clear differences in ADG. After the second vaccination, however, ADFI and DG of IM strongly increases (Schmidt et al, 2011;Batorek et al, 2012b;Weiler et al, 2013). We showed that this increase is very abrupt and noticeable within 1 week after the second injection.…”
Section: Discussionmentioning
confidence: 63%
“…Weiler et al (2013) observed that the strong increase in feed intake of IM after V2 mainly resulted from an increased feeding rate. In accordance with that study, we did not observe differences between treatment groups in the percentage of pigs spending time at feeding.…”
Section: Performancementioning
confidence: 93%
“…In accordance with that study, we did not observe differences between treatment groups in the percentage of pigs spending time at feeding. DFI of entire male pigs is suppressed by the presence of oestrogens and androgens (Weiler et al, 2013). Immunocastration reduces steroidogenic capacity and lowers the levels of these compounds, which can partly explain the increased feed intake.…”
Section: Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The turnover of intestinal cells could be influenced by the daily feed intake of the pigs. Weiler et al (2013) showed a significant positive correlation between the feed intake rate and the skatole concentration of barrows and immunocastrates, which both have high daily feed intakes. They speculate that this effect could be explained by changes in the intestinal microbial composition of pigs with a high daily feed intake or a difference in cell turnover leading to higher amounts of cell debris.…”
Section: Boar Taintmentioning
confidence: 96%